On the identities of the rafting crabs Cancer depressus Fabricius, 1775, Cancer squamosus Herbst, 1790, Plagusia immaculata Lamarck, 1818, and Plagusia tuberculata Lamarck, 1818 (Crustacea: Decapoda: Brachyura: Plagusiidae) - Schubart, C.D. (2014)
Raffles Bulletin of Zoology